Effect and fate study with blue mussels and microplastic in a laboratory experiment - Aurelia Laubscher; Thea Hamm; Mark Lenz (PANGAEA, 2021)
Adult blue mussels (Mytilus spp.) were exposed to microplastic particles in a controlled laboratory experiment. The study was conducted to investigate I) the effect of polystyrene particles (spherical PS beads, 40μm) on the filtration of mussels and II) the fate of PS beads within the experimental set up. The data was obtained in May and June 2019 with mussels collected from the Kiel Fjord, Germany. The mussels were exposed in a closed system to an intended initial microplastic concentration of 0.4 and 40 PS beads/ml. To correct for deviations from these two concentrations, the measured PS bead concentrations were used. Mussels were exposed to microplastic for 2 hours, followed by a 48 hours depuration phase in filtered sea water. Clearance rate of the food algae Rhodomonas baltica was measured during the first hour of exposure. The fate of PS beads was determined after exposure and after depuration in four compartments: exposure water, feces, softbody, depuration water. Additionally, the loss of microplastic was determined to obtain a complete mass balance.